High concentrations of Cu and Zn in the surface sediments are not necessarily related to high total organic matter in the sediments: an evidence of the metal data in the ignited sediments of the intertidal and drainage areas - Yap, Chee Kong (Malaysian Society of Applied Biology, 2008)
Fine-grained sediments tend to have relatively high metal concentrations, due in part to the high specific surface of the smaller particles. This enrichment is mainly due to surface adsorption and ionic attraction (Chen and Stevenson, 1986). However, in order to confirm and to enhance the understanding about this knowledge, the following comparative study and correlation analysis between mud and sandy sediments and between polluted and unpolluted sediments with different loss of ignitions were conducted. The objective of this study is to investigate and to prove that the high concentrations of Cu and Zn are not necessarily related to high total organic matter in the sediments.